25.9k views
18 votes
Find the formula for g(x) if it is known that (x-3)=2x-6

User Xoundboy
by
4.7k points

1 Answer

11 votes

Answer: g(x) = 2*x

Explanation:

We want to find the formula of g(x) if we know that g(x - 3) = 2*x - 6

Well, the first step is to find the expression (x - 3) = y in the g(x - 3)

Then:

g(x - 3) = 2*x - 6 = 2*x - 2*3

Now we can just take the common factor 2, and write this as:

2*x -2*3 = 2*(x - 3) = 2*y

then:

g( x - 3) = g(y) = 2*y

if we just replace x by y, we get:

g(x) = 2*x

This is the formula of g(x)

User Abhishek Nalin
by
4.7k points